Consumer behavior : buying, having, and being - Solomon, Michael R (Pearson, 2015)
For undergraduate and MBA courses in consumer behavior. Solomon goes beyond the discussion of why people buy things and explores how products, services, and consumption activities contribute to shape people's social experiences.